Multiparameter Optimization of Trypanocidal Cruzain Inhibitors With In Vivo Activity and Favorable Pharmacokinetics - Pauli, Ivani; Rezende Jr., Celso de O.; Slafer, Brian W.; Dessoy, Marco A.; de Souza, Mariana L.; Ferreira, Leonardo L. G.; Adjanohun, Abraham L. M.; Ferreira, Rafaela S.; Magalhães, Luma G.; Krogh, Renata; Michelan-Duarte, Simone; Del Pintor, Ricardo Vaz; et al. (Frontiers in Pharmacology, 2022)
Cruzain, the main cysteine protease of Trypanosoma cruzi, plays key roles in all stages of the parasite’s life cycle, including nutrition acquisition, differentiation, evasion of the host immune system and invasion of host cells. Thus, inhibition of this validated target may lead to the development of novel drugs for the treatment of Chagas disease. In this study, a multiparameter optimization (MPO) approach, molecular modeling and structure-activity relationships (SARs) were employed for the identification of new benzimidazole derivatives as potent competitive inhibitors of cruzain with trypanocidal activity and suitable pharmacokinetics. Extensive pharmacokinetic studies enabled the identification of metabolically stable and permeable compounds with high selectivity indices. CYP3A4 was found to be involved in the main metabolic pathway, and the identification of metabolic soft spots provided insights into molecular optimization. Compound 28, which showed a promising trade-off between pharmacodynamics and pharmacokinetics, caused no acute toxicity and reduced parasite burden both in vitro and in vivo.